Business Analysis of Antimony Between PT Timah-Mitsubishi-Yamanaka - Purwoko, Purwoko; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2013)
PT Timah (Persero) Tbk is the State Owned Enterprises that do tin mining business integrated starting from exploration, mining, smelting and marketing. The company set a target revenue growth of at least 15% per year by the company's business development strategy year (Albar, Alwin, personal interview, 10/9/2012). Inorganic Chemical Unit is a business unit of Mitsubishi Corporation that provides services and products, ethanol, methanol, ammonia, sulfuric acid, fertilizers, mining products and other. Yamanaka & Co Ltd has a copper smelting business, metallic materials, electronic materials, chemical industry, and experienced more than 20 years to produce antimony trioxide. Since the 2009 China as the supplier of the world's largest antimony metal (82%) regulate antimoni industry in the country, one of which implements the antimony metal export quota and prevent illegal mining or smuggling activities. This brings Chinese policies impact antimony metal supply deficit in global market and lead to a price increase from USD 5,500/ton in 2007 reached peak USD 17,200/ton in 2011 and USD 13,400/ton in June 2012. According to projections made by Mitsubishi Corporation, world consumption antimony in 2016 for 241,650 tonnes with supply of 206,460 tons so that there will be a supply shortage 35,190 tons. Antimony smelting plant requires a total project cost of $ 16,851,655 and financial analysis of the business of appealing to run because of the calculation of the financial projections all provide good indicators, namely: IRR 110.02%, NPV of USD 30,641,727; ROI 55.8%; PBP 1.1 years and PI 7.5. This situation is captured as a business opportunity by PT Timah (Persero) Tbk, Mitsubishi Corporation and Yamanaka Co Ltd is planning to form a strategic alliance Joint Venture Company (JV Co) with antimony smelting plant established in Indonesia with a capacity of 5,000 tons / year. The sales target for the Japanese market as much as 3,000 tons / year, South Korea targeted 1,000 tons / year and the rest for the Indian market, Thailand, Hong Kong, Europe and the Americas allocated a maximum of 1,000 tons / year. Keywords : antimony business, strategic alliance, business analysis of antimony, antimony metal, antimony smelting project.